JOAZEIRO, Edna Maria Goulart. Estágio Supervisionado: Experiência e conhecimento. Santo André, SP: ESETec Editores Associados, 2002. 171 p. - Edna Maria Goulart Joazeiro (Universidade Estadual de Campinas, 2015)
Resenha do livro